Divorce Due to Online Gambling in Indonesian Religious Courts: Legal Certainty and Women’s Protection in Islamic and Positive Law - Fakhriyah Annisa Afroo; Wevy Efticha Sary (Supremasi Hukum: Jurnal Penelitian Hukum, 2025)
The rise of online gambling in Indonesia has created serious family and legal problems. When husbands become addicted, financial neglect, debt accumulation, and domestic conflict often lead to divorce, leaving women as the most affected group. This study analyzes legal certainty and women’s protection in divorce cases caused by online gambling from both Islamic and positive law perspectives. Using a normative juridical method with statutory, conceptual, and case approaches, the research examines relevant laws and Religious Court decisions in Bengkulu. The results show that legal certainty is guaranteed through consistent court procedures and statutory frameworks such as the Marriage Law, Government Regulation No. 9 of 1975, the Compilation of Islamic Law, and the ITE Law, which classify gambling as a legitimate ground for divorce. Women’s protection is realized through iddah maintenance, mut’ah, custody rights, and division of joint property. This study’s novelty lies in integrating Islamic and national law analyses to reveal how legal certainty principles are operationalized in court practice to ensure substantive justice for women affected by online gambling–related divorces.